References Values of Fetal Heart Myocardial Volume by Three-Dimensional Ultrasound using Spatiotemporal Image Correlation and Virtual Organ Computer-Aided Analysis Methods and Their Applicability in Pregestational Diabetic Women - Melo Júnior, José Francisco; Bravo-valenzuela, Nathalie Jeanne; Nardozza, Luciano Marcondes Machado; Peixoto, Alberto Borges; Mattar, Rosiane; Martins, Wellington P.; Pares, David Baptista da Silva; Araujo Júnior, Edward (American Journal of Perinatology, 2019)
Objective To determine reference values for myocardial volume of the fetal heart using three-dimensional ultrasound with spatiotemporal image correlation (STIC) and virtual organ computer-aided analysis (VOCAL) and to assess their applicability in women with pregestational diabetes.Study Design This retrospective cross-sectional study included 177 normal pregnant women with fetuses between 200/7 and 336/7 weeks of age. Fetal cardiac volumes were collected using the STIC method, and myocardial volume was obtained by subtraction of the intracavitary volumes using the VOCAL 30-degree method. Intra- and interobserver reproducibility values were determined using the concordance correlation coefficient (CCC). Sixteen women with pregestational diabetes mellitus were evaluated for validation.Results There was a strong correlation between fetal myocardial volume and gestational age (R2 = 0.82). Intra- and interobserver reproducibility values were excellent and moderate, respectively, with CCCs of 0.99 and 0.83, respectively. There was no significant difference in mean fetal myocardial volume between normal pregnant women and those with pregestational diabetes (p = 0.64).Conclusion Reference values for myocardial volume of the fetal heart were determined in normal pregnant women and were not statistically different from those in women with pregestational diabetes mellitus.
Keywords: fetal heart; myocardium; three-dimensional ultrasound; virtual organ computer-aided analysis; reference values; pregestational diabetes mellitus